Comparison of Clinical Characteristics and Neutrophil Values in Omental Infarction and Acute Appendicitis in Children - Ya-Ling Yang; Ying-Hsien Huang; Mao-Meng Tiao; Kuo-Shu Tang; Fu-Chen Huang; Shin-Yi Lee (Pediatrics and Neonatology)
Omental infarction is a rare occurrence in children. It is often diagnosed during surgery for suspected appendicitis. This study investigated the use of clinical and laboratory data for distinguishing between omental infarction and acute appendicitis. Methods: Seven patients with surgically and pathologically proven omental infarction and 28 age- and sex-matched patients with acute appendicitis were included in this study. The clinical characteristics, imaging study results and laboratory data were analyzed. Results: All 35 patients had right lower quadrant abdominal pain at presentation. The frequency of nausea and fever were significantly lower in the omental infarction group compared with the acute appendicitis group (p< 0.001 and p= 0.018, respectively). In laboratory studies, the white blood cell count, C-reactive protein value and neutrophil percentage were all higher in the acute appendicitis group compared with the omental infarction group (p= 0.001, p< 0.001, and p= 0.008, respectively). It was possible to separate patients with omental infarction from those with acute appendicitis based on a neutrophil percentage of less than 77% (sensitivity 100%, specificity 100%). Conclusions: Results of the current study suggest that omental infarction should be considered as a possible diagnosis in patients presenting with right lower quadrant abdominal pain without nausea or fever, and with a neutrophil percentage below 77%.